2019
DOI: 10.1002/jbio.201800298
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of brain functional connectivity in patients with mild cognitive impairment: A functional near‐infrared spectroscopy (fNIRS) study

Abstract: This study examines brain functional connectivity in both cognitively normal seniors and patients with mild cognitive impairment (MCI) to elucidate prospective markers of MCI. A homemade four‐channel functional near‐infrared spectroscopy (fNIRS) system was employed to measure hemodynamic responses in the subjects' prefrontal cortex during a resting state, an oddball task, a 1‐back task, and a verbal fluency task. Brain functional connectivity was calculated as the Pearson correlation coefficients between fNIRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…MCI patients showed a decreased connectivity compared to HCs most notably in the PFC, as well as positive correlations with cognitive performance assessed by means of the MMSE and the Montreal Cognitive Assessment. Significant differences between MCI patients and HCs in inter-hemispheric connectivity during resting-state, as well as letter and category fluency tasks, were also reported by Nguyen et al [73], thus suggesting that intra-vs. inter-hemispheric connectivity could serve as marker to discriminate MCI from healthy subjects.…”
Section: Functional Resting-statesupporting
confidence: 68%
See 2 more Smart Citations
“…MCI patients showed a decreased connectivity compared to HCs most notably in the PFC, as well as positive correlations with cognitive performance assessed by means of the MMSE and the Montreal Cognitive Assessment. Significant differences between MCI patients and HCs in inter-hemispheric connectivity during resting-state, as well as letter and category fluency tasks, were also reported by Nguyen et al [73], thus suggesting that intra-vs. inter-hemispheric connectivity could serve as marker to discriminate MCI from healthy subjects.…”
Section: Functional Resting-statesupporting
confidence: 68%
“…We have therefore focused our attention on the current state-of-the-art of fNIRS applications dealing with motor and cognitive disability in the most frequent chronic neurological disorders of the elderly, namely PD and the AD continuum and MS as the most frequent chronic neurological disease of young and middle-aged adults. Our results reveal that AD and MCI are the most frequently addressed conditions by a wide variety of fNIRS applications, ranging from the monitoring of tissue oxygenation and vasomotor reactivity [65][66][67][68][69][70], to the analysis of resting-state conditions [64,[71][72][73], the assessment of cognitive functions by means of memory and verbal fluency tasks [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93], visuospatial functions [94,95] and other ecological applications [96,97]. Within the broad context of PD and MS, reviewed studies were more focused on the assessment of motor functions [51,[53][54][55][56]109,110,112].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent systemic review including 36 articles over the past two decades suggests that patients with MCI and AD have impaired frontal and long-range connectivity in the resting state fMRI ( Yeung and Chan, 2020 ), which was also observed in a recent study ( Yoo and Hong, 2019 ). Task-related functional connectivity analysis suggests that the number and strength of prefrontal functional connections increased during a working memory task ( Yu et al, 2020 ) but left and inter-hemispheric connectivity during a verbal fluency test were lower ( Nguyen et al, 2019 ) in the patients with MCI compared to healthy controls. This could indicate the use of compensatory mechanisms in the prefrontal cortex as a result of impaired default connectivity in MCI patients.…”
Section: Clinical Application Of Fnirsmentioning
confidence: 99%
“…Through studies over the past decade, researchers have demonstrated the feasibility of using fNIRS to identify reduced cerebral oxygenation either in the resting state or the task period, such as during word retrieval, memory tasks, motor tasks, and visuospatial perception [28]. In the resting-state cases, altered connectivity [29][30][31] and fluctuations [32][33][34][35][36] of cerebral oxygenation have been reported in MCI and AD groups. This difference is associated with the dysregulation of information integration in the patient's brain.…”
Section: Introductionmentioning
confidence: 99%